Ciclo diário da temperatura de brilho do topo de nuvens e características da precipitação em Cuiarana-PA - DUARTE, Christopher Henrique de Almeida (2019)
This study used satellite data in the infrared channel, which satellite images containing cloud top brightness temperature information in the infrared channel, the period from 2000 to 2015 in order to investigate the daily cycle of the top brightness temperature clouds, concomitant with the surface data of automatic weather station installed on Coastal Studies Center Modesto Rodrigues (UFPA, latitude 0°39’55’’S and longitude 47°17’05’’W) in Cuiarana of Village, country of Salinópolis, northeastern Pará. The methodology consisted of: i) analyze the satellite data through vertical profiles of annual and seasonal daily cycle of the total number of pixels of cloud top brightness temperature throughout the 11 and troposphere layers (-85°C < Tb < 18°C) to 10°C, except that the layer 1 has the range of 3°C (15°C < Tb < 18°C), from 15°C on the middle region of northeastern Pará and 100 bars of 0,0015° x 0,0015 ° from latitude and longitude for the period 2000 to 2015; and ii) examine the annual and seasonal daily cycle of various meteorological variables, focusing on precipitation, obtained by the weather station installed in Cuiarana for the period 2012 to 2015. The results showed that the daily cycle of the top cloud brightness temperature, layer 2 has a configuration similar to that observed in the annual cycle of daily rainfall in Cuiarana, which were found maximum during the night and early morning period, and minimum in the evening. The layers situated between the low and high a1ta troposphere (3 to 6; -35°C < Tb < 5°C) have high numbers of pixels in the top Tb clouds, indicating that the clouds are more numerous and deep. The upper layers (7, 8 and 9), with lower temperatures (-65°C < Tb < -35°C) are associated with the existence of large vertical development clouds (cumulonimbus). In the annual cycle of daily precipitation were observed maximum during the night, especially with 0,3 mm/30min values in at 02:00, 03:30 and 23:00 local time (HL), which coincides with the maxima observed in the annual daily cycle the total number of pixels of brightness temperature of the cloud top. Therefore, it is concluded that the night precipitation is more intense.